Pengembangan Perangkat Kooperatif Tipe NHT Berbasis Pendekatan Ilmiah pada Materi Asam Basa untuk Meningkatkan Sikap Ilmiah dan Hasil Belajar Kognitif Peserta Didik - Hasnawiyah, Hasnawiyah; Danial, Muhammad; Sanusi, Wahidah (Program Pasca Sarjana UNM, 2021)
The use of the right tools greatly determines the success of achieving the competence of students in learning. Learning tools that tend to be monotonous make students less actively involved in learning and less improve scientific attitudes and learning outcomes. The development of Chemistry learning tools based on a scientific approach in NHT model is expected to be effective in the classroom and help students in learning Chemistry. This development research aims to: 1) describe the development process of producing cooperative learning tools of NHT type based on a scientific approach; and 2) produce cooperative learning tools of NHT type based on scientific approaches that are valid, practical, and effective to improve scientific attitudes and learning outcomes on Acid-Base learning material. This research consists of the stages of defining (define), design, development, and dissemination (disseminate). The product developed was tested on students of class XI MIPA.3 at SMAN 8 Gowa of academic year 2019/2020. The product validity was tested by two expert assessors. This research includes the steps of the NHT model, namely preparation, group formation, problem discussion, calling the Member Number or Giving Answers, giving conclusions, and giving awards. The stages of this chemistry learning tool also refer to the scientific attitude approach that applies 5M, namely observing, asking, trying, associating/processing information/logic,and communicating to improve scientific attitudes and learning outcomes of students. The results of the study obtained: 1) the average value of product validity 3.76 (very valid); 2) scientific attitude questionnaire data = 3.07 (high); 3) THB's average N-Gain result is 0.83 (high); 4) teachers and students showed a very positive response with a percentage of 95.84% and 82.81%. Therefore, the conclusion of the study is the Chemistry learning tools based on the scientific approach in NHT model that had been developed in Chemistry learning on Acid-Base learning materials are valid, practical, and effective to improve the scientific attitude and learning outcomes of students.